2014
DOI: 10.1016/j.ijsu.2014.08.357
|View full text |Cite
|
Sign up to set email alerts
|

Incisional hernia in the elderly: Risk factors and clinical considerations

Abstract: Reparative surgery of the abdominal wall, to date uniquely characterized by the use of the mesh, should be considered an additional risk factor for the occurrence of incisional hernia. However, the low incarceration risk, the risk of recurrence, the relevant rate of postoperative pain and discomfort and complications associated with mesh repair, as small bowel obstruction, mesh infection, and entero-cutaneous fistula, suggest that the general indication for surgical treatment of incisional hernias, in a sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 79 publications
1
28
0
1
Order By: Relevance
“…In the Spanish National Registry of Incisional Hernia (EVEREG) increasing incisional hernia complication rates was observed from age > 70 years [49]. Therefore, it is very reasonable that the indication for surgery of an incisional hernia in an older patient should be carefully and critically considered [50].…”
Section: Age > 80 Yearsmentioning
confidence: 99%
“…In the Spanish National Registry of Incisional Hernia (EVEREG) increasing incisional hernia complication rates was observed from age > 70 years [49]. Therefore, it is very reasonable that the indication for surgery of an incisional hernia in an older patient should be carefully and critically considered [50].…”
Section: Age > 80 Yearsmentioning
confidence: 99%
“…It was also reported that recurrence rate is very low when prosthetic mesh repair was done and considered as a gold standard treatment. 4 Wound infection is another problem of mesh repair. In both type of surgical repairs ventral hernia and incisional Hernia type and method of repair is very important especially when prosthetic mesh repair planned.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of models, however, use post-operative variables that limit their use for patient counseling and in implementing pre-operative or intra-operative interventions (1, 2, 4, 5, 6, 7). The HERNIAscore is a VIH risk assessment tool that utilizes only preoperative variables and predictable intra-operative variables: body mass index (BMI), chronic obstructive pulmonary disease (COPD), and incision length (laparoscopic, extended laparoscopy, or laparotomy) (8).…”
Section: Introductionmentioning
confidence: 99%